An imaging method for impact localization using metal-core piezoelectric fiber rosettes. (November 2015) - Zhang, Chao; Qiu, Jinhao; Ji, Hongli; Shan, Shengbo
As a novel piezoelectric device, metal-core piezoelectric fiber has great potential to be a structurally integrated transducer for guided-wave structural health monitoring. Compared with common piezoelectric ceramics with in-plane isotropic characteristic, metal-core piezoelectric fiber exhibits unique directivity in Lamb wave sensing which can locate the direction of the impact without any information about time of flight or speed of propagation. This article introduces a metal-core piezoelectric fiber rosette that contains three metal-core piezoelectric fibers with an angle of 120° between adjacent metal-core piezoelectric fibers. To simplify the process of placing three metal-core piezoelectric fibers onto the structure and improve the performance of metal-core piezoelectric fiber rosettes, a method for packaging metal-core piezoelectric fiber rosette is presented. By coupling the piezoelectric effect to the wave strain field, the directivity of metal-core piezoelectric fiber is derived. In order to determine the direction of an incoming wave, previous work measures the amplitudes of metal-core piezoelectric fibers and calculates the wave direction by the rosette principles. However, the calculated wave direction is very sensitive to the measurement error, which comes from unavoidable sensor noise and complex dispersive effect in actual application. To improve the accuracy, a new method that combines an imaging method with the rosette approach is proposed. Its accuracy is validated by experiments, and the phenomena in experiments are also discussed.